PERANCANGAN ARSITEKTUR INFORMASI UNTUK MENDUKUNG KEBERLANGSUNGAN PROSES BISNIS ENTERPRISE WIDE - C Wardiyono (CKI ON SPOT, 2016)
In running its business processes, an organization formed which describes the overall organizational structure of business units of the organization to execute the business functions and coordination in the achievement of organizational goals. But in its application sometimes lack the power tie or clear coordination among business units and among its functions for a wide range of interests. Egocentric locally in each business unit functions in effect on performance and interaction between information systems in each unit and function, resulting in data integration was not optimal and developed information system is not optimal. Besides this, the changes that occur in the system environment, for example the growth of an organization, competition, to seize the opportunity and other things can affect the performance of the information system. In this case the information system must be able to accommodate any changes that occur in the organization, so that the business processes of the organization can continue to run in accordance with its function. This paper will discuss the design of an integrated information architecture based on the relevance of each function within the organization, with the view that an information system is an integral basic components that have the same characteristics and do not separate. Each of these basic components are defined and analyzed linkage function, so as to overcome any problems that arise in the organization, and can accommodate perubahanperubahan happened. The model is expected to be built to current guidelines do in the future development of information systems. To complete the study of the research, in this paper comes to the discussion of case studies in a government agency.